Between Languages and Cultures: Gary Shteyngart as a Global Author. - Bryla, Martyna Marika (Comares, 2020)
In this essay, I approach Shteyngart as a writer who has forged a voice of his own and built a successful literary career between cultures and languages. To do so, I will use the concept of limen as a fertile space where diverse cultural and linguistic references collide and collude, through the processes of creative juxtaposition, negotiation, and translation, to produce a new literary quality marked by transcultural and translingual imagination and thus attuned to the interconnectedness of today’s globalized world. Rather than think of Shteyngart as an ethnic author, I propose to interpret his writing and the public persona he constructed in the course of his literary career in global terms which, in a broader perspective, speak to the exciting yet precarious realities of liquid modernity (Bauman, 2000).
Cuento con el permiso de la editorial Comares para publicar la versión pre-print en acceso abierto.
Keywords: Shteyngart, Gary - Crítica e interpretación; Gary Shteyngart; Limen; Liminality; Soviet Union; Russia; Cold War; United States of America; Identity; Global author; World literature; Liquid modernity